Effect of influenza vaccination on excess deaths occurring during periods of high circulation of influenza: cohort study in elderly people - Armstrong, Ben G (BMJ Publishing Group Ltd., 2004)
Objective To estimate the protection against death provided by vaccination against influenza. Design Prospective cohort follow up supplemented by weekly national counts of influenza confirmed in the community. Setting Primary care. Participants 24 535 patients aged over 75 years from 73 general practices in Great Britain. Main outcome measure Death. Results In unvaccinated members of the cohort daily all cause mortality was strongly associated with an index of influenza circulating in the population (mortality ratio 1.16, 95% confidence interval 1.04 to 1.29 at 90th centile of circulating influenza). The association was strongest for respiratory deaths but was also present for cardiovascular deaths. In contrast, in vaccinated people mortality from any cause was not associated with circulating influenza. The difference in patterns between vaccinated and unvaccinated people could not easily be due to chance (P = 0.02, all causes). Conclusions This study, using a novel and robust approach to control for confounding, provides robust evidence of a protective effect on mortality of vaccination against influenza.